Self-control and academic performance. A comprehensive review and empirical study (Encuentros, 2024)
Self-control, a pivotal determinant in the regulation of human behavior, has consistently demonstrated a strong association with a plethora of advantages, particularly notable in the context of academic accomplishments. This scholarly article presents a comprehensive literature review that delves deeply into the multifaceted construct of self-control, shedding light on its intricate psychological underpinnings. Furthermore, it offers an extensive descriptive study with the principal objective of scrutinizing the interrelationship between self-control and academic performance, as assessed by academic grades, within a carefully selected sample of 161 students pursuing degrees in business engineering. The evaluation hinges on the deployment of the Abbreviated Self-Control Scale. The research findings divulge a moderately robust and positively significant correlation between these key variables, characterized by a Spearman's rₛ coefficient of 0.317, signifying statistical significance at a 99% confidence level. These outcomes undeniably substantiate a meaningful connection between self-control and academic performance, thereby contributing to an enhanced understanding of the profound impact of self-control on academic success. This study constitutes a valuable addition to the existing body of knowledge and paves the way for future research endeavors within this domain.
Keywords: Education; Self-control; Academic performance; College students